Formulation And Evaluation Of Lip Scrub Using Beetroot Extract (Beta Vulgaris L.) As A Natural Colorant - Dikta Anggraini Miftahul Jannah; Tatiana Siska Wardani; Rahmat Hidayat (CV. AFDIFAL MAJU BERKAH, 2026)
Lips are prone to dryness due to the thin stratum corneum layer and environmental exposure, driving the need for natural dyes to replace synthetic carcinogenic risks such as Rhodamine B. This study aims to formulate a lip scrub extract of beetroot (Beta vulgaris L.) at a concentration of 5%, 10%, 15%, measure betacyanin levels, and evaluate physical quality. Quantitative experimental types were conducted at the Duta Bangsa University Laboratory in Surakarta (April-June 2025); beetroot population in Boyolali, tuber samples aged 3-6 months; UV-Vis spectrophotometer instrument, rotary evaporator; SPSS analysis (ANOVA). The results showed a yield of 17.5% of the crude drug, 16.81% of the extract, 1.145 mg/L of betacyanin, good homogeneity, pH 5.33-6.03, no irritation (9 panelists), although the width of 3.75-4.58 cm was suboptimal. Conclusion: the formulation is safe and stable as a natural dye, although pigment stability needs optimization.